PP.03.19: MORNING SURGE AND CARDIOVASCULAR RISK PROFILE IN DIFFERENT SUBSETS OF HYPERTENSIVE PATIENTS. (June 2015) - Varga, A.; Voidazan, S.; Magdas, A.; Carasca, E.; Podoleanu, C.; Tatar, R.; Tilea, I.
Abstract : Objective: To evaluate the relationship concerning blood pressure (BP) morning surge and cardiovascular risk profile in hypertensive patients. BP morning surge might imply higher cardiovascular risk. Design and method: In forty-four men and 36 women, mean age 60.56 ± 12.19 yrs, hypertensive patients consecutively submitted for clinical evaluation, standard 24 h ambulatory blood pressure monitoring (ABPM) was performed using a Meditech™ ABPM-05 device; routine blood samples and echocardiography examination were assess. Sleep-through morning surge was used to define BP morning surge, as the difference between the morning pressure during the first 2 hours after awakening and the average of the lowest night-time BP, using the submission that a systolic morning BP surge less than 20 mmHg is not associated with increased risk. Ambulatory pulse pressure (PP) is a potent cardiovascular risk factor. Other cardiovascular risk factors such as smoking status, body mass index (BMI), type 2 diabetes mellitus, total cholesterol were computed. Estimated Glomerular Filtration Rate (eGRF) and left ventricular hypertrophy (LVH) as target organ damage (TOD) markers were subtracted. Results: Evaluating ABPM's in all patients, pulse pressure average was 56.70 ± 14.22 mmHg. In 23 hypertensive patients with widened PP (>60mmHg), 65.2% patients presented BP morning surge but no significant correlation between BP morning surge and PP, no influence of age (>60yrs). BP morning surge was found not to be influenced by any independent cardiovascular risk factor taken into account: smoking status, presence of BMI, type 2 diabetes mellitus, eGRF and total cholesterol (p > 0.05). Strong statistical correlation has occurred between PP > 60mmHg and eGRF rate (p = 0.001). Correlated with target organ damage, BP morning surge was strongly associated to LVH with stronger association in-group aged < 60 yrs. (p = 0.007). Multivariate logistic regression applied outlines that BP morning surge is dependent influenced by the simultaneous presence of the diabetes (p = 0.05), widened PP (p = 0.02) and LVH (p = 0.02) in hypertensive patients. Conclusions: In our study, BP morning surge was not identified as being influenced by the presence of individual cardiovascular risk factors, but increase the poor prognosis in hypertensive patients with different cardiovascular risk profile.